Integrasi Pendidikan Lingkungan dalam Pembelajaran: Pemanfaatan Sampah sebagai Media Edukatif untuk Anak TK - Ni Wayan Martini Jovita Yanti; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the integration of environmental education into early childhood learning activities at TK Prawidya Dharma Demulih through the use of recycled waste as a creative and educational learning medium. The study was motivated by the low environmental awareness among children and the limited use of environmentally themed learning media in the institution. A qualitative descriptive approach was applied using the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The findings reveal that employing a recycled-material spinner game enhanced children’s understanding of environmental cleanliness and encouraged environmentally responsible behavior through playful learning activities. The children showed strong enthusiasm, participated actively, and began to develop habits related to cleanliness after the learning sessions. Moreover, teachers gained new insights into designing innovative and functional learning media using discarded materials. Overall, the use of recycled waste as an educational tool proved effective in fostering environmental awareness while supporting creativity and meaningful learning experiences for early childhood learners..